Microbiology for Earth Scientists - Kirk, Matthew F. (Open textbook library., 2024)
Microorganisms are the most abundant form of life on Earth and in recent decades it has become increasingly clear that their collective activities are one of the dominant forces shaping the Earth. This book provides earth scientists with an introduction to microbiology and a look at the ways microorganisms are important to their area of expertise. The first part of this book summarizes some basic information about microorganisms, including a discussion of their diversity, physical properties, and metabolisms. From there, the second and third portions of the book are organized around the two-way interactions between microorganisms and their environments. The second portion of the book considers the ways that environmental conditions help determine distributions of microbial activity, including chapters focused on thermodynamic, kinetic, and biological factors. The third and final portion of the book examines the impacts of microbes on their environments. These impacts are placed within the context of earth system science, with chapters focused on impacts to the lithosphere, atmosphere, and hydrosphere. In these chapters, emphasis is placed on microbial impacts to greenhouse gas levels and the quality of water resources, underscoring the relevance of microbiology to environmental concerns of keen interest in the earth science community and beyond. This book is specifically designed for earth science students and can provide a helpful free resource for students in Geomicrobiology courses. However, portions of the book can also have value for students and professionals from any field who are interested in environmental microbiology.